2006
DOI: 10.1007/s00294-005-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the HOG-signalling system in fungi

Abstract: Signal transduction pathways play crucial roles in cellular adaptation to environmental changes. In this study, we employed comparative genomics to analyse the high osmolarity glycerol pathway in fungi. This system contains several signalling modules that are used throughout eukaryotic evolution, such as a mitogen-activated protein kinase and a phosphorelay module. Here we describe the identification of pathway components in 20 fungal species. Although certain proteins proved difficult to identify due to low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 73 publications
5
60
2
Order By: Relevance
“…They found that the Sln1 branch dominated the activation dynamics of the HOG pathway and allowed cells to integrate fast fluctuating inputs from the environment. This observation is interesting when contrasted with the fact that while yeast has two branches that feed into the osmoadaptation pathway, it is the faster Sln1 branch, and not the Sho1 branch, that is conserved in fungi, indicating the importance of a fast response to osmolar changes in the environment (Furukawa et al, 2005;Krantz et al, 2006). Their results also suggest that the HOG pathway bandwidth is likely to be limited by the deactivation rates of components at or downstream of Pbs2, thereby highlighting the role of pathway phosphatases as an avenue for future investigation.…”
contrasting
confidence: 39%
“…They found that the Sln1 branch dominated the activation dynamics of the HOG pathway and allowed cells to integrate fast fluctuating inputs from the environment. This observation is interesting when contrasted with the fact that while yeast has two branches that feed into the osmoadaptation pathway, it is the faster Sln1 branch, and not the Sho1 branch, that is conserved in fungi, indicating the importance of a fast response to osmolar changes in the environment (Furukawa et al, 2005;Krantz et al, 2006). Their results also suggest that the HOG pathway bandwidth is likely to be limited by the deactivation rates of components at or downstream of Pbs2, thereby highlighting the role of pathway phosphatases as an avenue for future investigation.…”
contrasting
confidence: 39%
“…The transduction pathway that controls turgor regulation is the osmotic MAP kinase pathway. The pathway has been characterized most completely in yeast (O'Rourke et al, 2002), and is found in numerous fungal species on the basis of comparative genomics (Krantz et al, 2006). In N. crassa, a histidine kinase sensor OS-1 (Alex et al, 1996;Miller et al, 2002) and an associated response regulator RRG-1 (Jones et al, 2007) function upstream of the MAPKKK OS-4 and MAPKK OS-5 (Fujimura et al, 2003), and MAPK OS-2 (Zhang et al, 2002), to elicit both glycerol accumulation (Noguchi et al, 2007) and ion accumulation (Lew et al, 2006) during turgor recovery after hyperosmotic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Sho1 branch in many fungi does not seem to be connected to Pbs2 homologues nor involved in responding to osmotic stress. [23][24][25] …”
Section: Resultsmentioning
confidence: 99%